Capillary‐channeled polymer (C‐CP) fibers for the rapid extraction of proteins from urine matrices prior to detection with MALDI‐MS. Issue 5 (18th March 2015) - Manard, Benjamin T.; Jones, Sarah M. H.; Marcus, R. Kenneth; Capelo Martínez, José Luis; Lodeiro, Carlos; Santos, Hugo M.
<x xml:space="preserve">Abstract</x> Purpose While MS is a powerful tool for biomarker determinations, the high salt content and the small molecules present in urine poses incredible challenges. Separation/extraction methods must be employed for the isolation of target species at relevant concentrations. Micropipette tips packed with capillary‐channeled polymer (C‐CP) fibers are employed for the SPE of proteins from a synthetic and a certified urine matrix. Experimental design Extractions are performed utilizing a very simple centrifugation method to spin‐down species through the C‐CP fiber tips. Proteins adsorb to the hydrophobic polypropylene fibers and are eluted in a solvent suitable for MALDI‐MS analysis. Figures of merit are determined for representative compounds β2‐microglobulin, retinol binding protein, and transferrin. Results The optimum protein processing included a 100 μL aqueous rinse and an elution solvent composition was 10 μL of 55:45 ACN:water (with triflouroacetic acid). MALDI‐MS responses for the target proteins are improved from nondetectable levels to eventually yield LOD ranging from 5 to 180 nM in 1 μL aliquots. Conclusion and clinical relevance C‐CP fiber tips offer a plethora of advantages including low materials costs, high throughput, microvolume processing, and the determination of sub‐nanogram quantities of analyte; allowing determination of biomarkers that are otherwise undetectable in urine matrices.